Microalgae as expression systems for recombinant protein production - Luis Muñoz-Solórzano; Kate Willis-Ureña; Sebastián Valverde-Rojas; Montserrat Jarquín-Cordero; Luis Barboza-Fallas (Tecnología en Marcha)
In the field of biotechnology, recombinant proteins have revolutionized many industries, including pharmaceuticals, agriculture, and bioenergy. By producing high-value proteins in heterologous hosts, cell factories may offer a more efficient, cost-effective, scalable, and environmentally friendly solution to traditional protein production and extraction methods, which can be highly laborious and resource intensive. Microalgae have emerged as attractive hosts due to their Generally Recognized as Safe (GRAS) status, versatile metabolism, genetic diversity between species, ease of cultivation and scale-up, and general cost-effectiveness. For genetic engineering, their capability for complex protein synthesis and post-translational modifications and ease of transformation in comparison with chasses outside of their category make microalgae an advantageous solution on many fronts. Microalgae can be transformed to enable efficient protein expression, most commonly in the nucleus and the chloroplast, each with their specific advantages and limitations. The present literature review compiles some of the techniques, features, and latest advances related to recombinant protein production in microalgae, exploring different genetic transformation techniques and their limitations. Recombinant protein production is only one of the many processes that can become more sustainable and efficient by using microalgae as a platform.